ADCtotal ratio and D ratio derived from intravoxel incoherent motion early after TACE are independent predictors for survival in hepatocellular carcinoma. Issue 3 (9th March 2017) - Wu, Lifang; Xu, Pengju; Rao, Shengxiang; Yang, Li; Chen, Caizhong; Liu, Hao; Fu, Caixia; Zeng, Mengsu
Abstract : Purpose: To explore the threshold of intravoxel incoherent motion (IVIM) parameters, apparent diffusion coefficient [ADCtotal and ADC(0, 500) ] ratios 24–48 hours after transarterial chemoembolization (TACE) to assess early response in patients with unresectable hepatocellular carcinoma (HCC) and to compare the association between diffusion‐weighted imaging with the intravoxel incoherent motion (IVIM‐DWI) and mRECIST with survival. Materials and Methods: Institutional Review Board approval and informed consent were obtained for this prospective study. There were 30 patients undergoing 1.5T magnetic resonance imaging (MRI) with IVIM‐DWI of 12 b values (0, 10, 20, 30, 40, 50, 70, 100, 200, 300, 500, 800 s/mm 2 ) 1 week before and 24–48 hours after TACE. Response was assessed with the change of true diffusion coefficient (D), pseudo‐diffusion coefficient (D*), perfusion fraction (PF), ADCtotal, and ADC(0, 500) values relative to baseline and with mRECIST. Receiver operating characteristic (ROC) curve analysis was used to explore the threshold of these parameters ratios. Kaplan–Meier, log‐rank tests, and the Cox hazard model were used to correlate the response variables with progression‐free survival (PFS) and to assess the incidence and potential clinical risk factors for PFS. Mann–Whitney U ‐test was used to compare the difference in parameters between different groups with progression within and beyond median PFS prior to TACE. Results: Median PFS was 99 days, within which 16 patients progressed. The threshold of ADCtotal ratio, D ratio, and ADC(0, 500) ratio were 13.1% ( P = 0.001), 7.0% ( P = 0.011), and 3.6% ( P = 0.018) with sensitivity and specificity of 78.6% and 87.5%, 85.7% and 62.5%, 78.6% and 75%, respectively. The predictive utility of ADCtotal ratio, D ratio, and ADC(0, 500) ratio for PFS were 0.848, 0.772, and 0.754, respectively. Survival analyses showed ADCtotal ratio, D ratio, ADC(0, 500) ratio, liver cirrhosis, and mRECIST had a significant effect on PFS ( P < 0.05). ADCtotal ratio and D ratio were independent predictors for 99‐day PFS ( P = 0.025, P = 0.036). There were no significant differences in pretreatment IVIM‐DWI parameters between PFS > 99‐day group and PFS ≤ 99‐day group with P values of 0.547 for D, 0.394 for D*, 0.575 for PF, 0.901 for ADC(0, 500), and 0.506 for ADCtotal, respectively. Conclusion: The ADCtotal ratio and D ratio 24–48 hours after TACE were independent predictors for response to TACE for HCC, and showed stronger association with PFS than mRECIST. Level of Evidence : 1 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:820–830